2007
DOI: 10.1515/znc-2007-3-408
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Effects of Tetrahydrophthalimides and Related Compounds

Abstract: This paper describes the antinociceptive effects of tetrahydrophthalimides and related compounds in mice. Twenty compounds were obtained by the reaction of cis-1,2,3,6-tetrahydrophthalic anhydride with appropriate amines, dehydration, and addition to the imidic double bond. They were analyzed in the writhing test at 10 mg/kg given intraperitoneally. The most active compound 2-benzyl-5-morpholin-4-yl-hexahydroisoindole-1,3-dione (19) was studied on formalin, capsaicin, glutamate and hot plate models. The antino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results of the evaluation of CME-Jul, CLF-Jul, and EAF-Jul at a dose of 10 mg/kg indicated that all the samples tested significantly reduced the nociception, but a greater result was observed for the non-polar fraction, CLF-Jul (64.4%) (Figure 3). Common drugs used in clinical treatments, such as aspirin and paracetamol, show inhibition around 35% in same conditions (Costa et al, 2007). After this trial result, it was determined the DI 50 (minimal dose able to inhibit 50% of writhings compared to the control group) of CLF-Jul (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the evaluation of CME-Jul, CLF-Jul, and EAF-Jul at a dose of 10 mg/kg indicated that all the samples tested significantly reduced the nociception, but a greater result was observed for the non-polar fraction, CLF-Jul (64.4%) (Figure 3). Common drugs used in clinical treatments, such as aspirin and paracetamol, show inhibition around 35% in same conditions (Costa et al, 2007). After this trial result, it was determined the DI 50 (minimal dose able to inhibit 50% of writhings compared to the control group) of CLF-Jul (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Since many years ago, plants have been employed with success to cure the more distinct ailments. Currently, modern medicinal chemistry is using new approaches and technologies that confirm the scientific evidence on the therapeutic efficacy of various medicinal plants, their isolated substances and derivatives (Filho, 2015;Alves, 2013;Cragg and Newman, 2013).…”
Section: Introductionmentioning
confidence: 99%